SEISMIC-GEOLOGICAL ANALYSIS OF THE SOUTH CASPIAN MEGA DEPRESSION EVOLUTIONARY DEVELOPMENT TO IDENTIFY HYDROCARBON ACCUMULATIONS - POGORELOVA, Elena; ABDULLA-ZADA, Murad; ABILHASANOVA, Lala; SHIKHMAMMADOVA, Telli (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. The South Caspian Mega Depression (SCMD) is a territory limited in the west by the Dziruly massif, in the east by the Western Turkmenian Depression (inclusive), in the north by the mountain structures of the Greater Caucasus, Greater Balkhan and in the south restricted by the Lesser Caucasus, Talysh and Albours (including the aquatic area of the Southern Caspian) which in turn is related to the South Caspian oil and gas mega-basin. In the geodynamic model, the SCMD represents the Caucasian segment of the Alpine-Himalayan folded belt (its intermountain part) with elements of the active stage of development inherent in this area – earthquakes, sea level changes, mud volcanism, etc.   Methods. This article examines the history of the development of SCMD based on data from geophysics, drilling, volcanology, geodynamics in order to identify accumulations of hydrocarbons. Seismogeological sections presented throughout the study area explain the complex geological structure and geodynamics, starting from the baikalian tectonic genesis and up to the present time. The clear boundaries of sedimentary basins and the island arcs surrounding them, which controlled lithology and stratigraphy, make it possible to predict probable petroleum source rock and oil and gas-producing rocks. Results. The construction of structural multi-temporal sediment surfaces in the Petrel program made it possible to trace the geological development of a certain segment (the South Caspian Aquatic Basin) of the studied territory, to clarify the influence of both long-lived deep and short-term local faults on the petrological composition of sediments and their thickness to determine the contours of possible objects of oil and gas formation. Conclusions. The approximation of the outlined oil and gas source rocks (by PetroMod modeling) stratigraphic units on the territory of Western Turkmenistan to the western part of the SCMD assumes the allocation of hydrocarbon sources in deep-submerged rocks in the rest of the territory. The combination of seismometry and volcanology data makes it possible not only to outline geological bodies on seismic profiles, but also to determine their density composition and chemistry by the speed of propagation of seismic waves.
Keywords: South Caspian Mega Depression; Greater Caucasus; Lesser Caucasus; Talysh; Alborz; geodynamic model; hydrocarbon sources